The Outflow Impact on the Size of the Narrow-line Region among Type 2 Active Galactic Nuclei - Kantapon Jensangjun; Suraphong Yuma (The Astrophysical Journal)
We present a study of the gas kinematics in narrow-line regions (NLRs) of 2009 Type 2 active galactic nuclei (AGNs) at z < 0.34. We construct [O iii ] λ 5007 emission-line images using publicly available broadband images from the Sloan Digital Sky Survey (SDSS). The [O iii ] emission areas of the samples, measured down to a rest-frame isophote of 1.4 × 10 ^−15 erg s ^−1 cm ^−2 arcsec ^−2 , range from 3.7 up to 224 kpc ^2 . With our broadband technique, we found a correlation between [O iii ] area and AGN luminosity inferred from the [O iii ] luminosity and the mid-infrared luminosity at rest-frame 15 μ m. The isophotal threshold used to determine the [O iii ] area affects the correlation strength in that a brighter isophote yields a stronger correlation between the [O iii ] area and AGN luminosity. The presence of gas outflows is examined by the ratio of the [O iii ] velocity dispersion to the stellar velocity dispersion ( σ _[O _iii _] / σ _⋆ > 1.4) using SDSS spectra. At a given luminosity, objects with and without outflows exhibit the same extent of [O iii ] emission. Their correlation between [O iii ] area and luminosity is almost identical. It is suggested that the size of NLRs is not affected by outflow mechanisms but rather by photoionization from the central AGNs.